Successful treatment of recurrent traumatic cardiac arrest due to splenic rupture in trauma resuscitation unit: a case report - Gu, Ruonan; Hu, Haimin; Zhao, Haiping; Shen, Yuhua; Gu, Hailun; Han, Weijie; Jiang, Gefei; Jiang, Shouyin (Frontiers in Medicine, 2025)
Recurrent traumatic cardiac arrest (rTCA) represents a critical emergency with mortality rates exceeding 96% and limited neurological recovery among survivors. High-quality evidence to guide standardized management remains scarce. We report the case of a 67-year-old male presenting with rTCA secondary to Grade IV splenic rupture following a high-impact traffic collision. Upon emergency department arrival, the patient experienced cardiac arrest, achieving temporary return of spontaneous circulation before a second arrest 8 min later due to massive intra-abdominal hemorrhage. Focused assessment with sonography for trauma (FAST) and diagnostic paracentesis confirmed splenic rupture as the primary cause. Due to persistent hemodynamic instability precluding transfer, emergency laparotomy was determined 10 min post-arrival and performed in the trauma resuscitation unit (TRU) 25 min latter. Intraoperatively, 2,500 mL of blood and 300 g of clots were evacuated, followed by splenectomy for definitive hemostasis. Aggressive resuscitation, including tranexamic acid, prothrombin complex concentrate, and packed red blood cell transfusion within 23 min, alongside multidisciplinary intensive care, facilitated hemodynamic stabilization within 48 h. Full neurological recovery was evident by day 5, with successful extubation on day 7 and discharge on day 25 with restored functional independence. This case highlights three key principles for rTCA management: (1) surgical strategy (laparotomy versus thoracotomy) and venue (TRU versus operating room) must be informed by integrated injury assessment and hemodynamic status; (2) early hemostatic control is critical to interrupting recurrent arrests; and (3) multimodal, goal-directed resuscitation and interdisciplinary collaboration are essential for optimizing survival and neurological outcomes. These insights offer a robust framework for trauma teams managing complex rTCA cases.